Rural School Psychological Services and Practical Graduate Training: A Cooperative Project - Goetz, Emily; Doerksen, Hart (Canadian Journal of Counselling and Psychotherapy, 2012)
A rural school district with no psychological services and a nearby university education clinic designed and implemented a short-term clinical programme for the district schools. The clinic team consisted of graduate interns in school psychology, a university faculty member, and the district elementary supervisor. Objectives for the project were defined by the district and the university. Forty-one children were assessed and received follow-up treatment. Objectives for the project were evaluatedand discussed. The rural placements where interns planned and worked in a programme with a district administrator and a university supervisor seemed to provide effective short-term service for the schools and a useful training experience for graduate students in school psychology.